Analisis perencanaan sistem jaringan pipa (plumbing) dan sistem reservoar air bersih pada bangunan gedung - Rian Hidayat; Athiah Safari; Elfiyusriningsih Syara (PADURAKSA: Jurnal Teknik Sipil Universitas Warmadewa, 2025)
The PKU Muhammadiyah UNIMUDA Sorong Hospital, located in Sorong Regency, West Papua, is currently in its initial phase of construction. This study aims to analyze the clean water demand, design the water distribution (plumbing) system, and estimate the construction costs of the plumbing and reservoir systems for the hospital's main building. The research method used is descriptive quantitative, utilizing primary data from field observations and secondary data such as architectural plans and technical standards. The water demand calculation is based on the Unit Plumbing Fixture Load (UPFL) method, referring to the Indonesian National Standard (SNI) 8153:2015. The results indicate that the water distribution system is designed by considering the reservoir capacity, pipe dimensions, minimum water pressure, and flow efficiency to support the hospital's operational needs sustainably. Cost estimation is presented in the form of a Bill of Quantities (BoQ), covering key components such as piping, pumps, and plumbing accessories. This research contributes as a technical reference for planning clean water systems in multi-story healthcare facilities and supports efficient and sustainable water management efforts in the West Papua region.